Given:
There are given the equation:
![(1-3x)^{(1)/(2)}-1=x](https://img.qammunity.org/2023/formulas/mathematics/college/rv25aq3ufu06fgn2fsjcxfm160ecr8yk9u.png)
Step-by-step explanation:
According to the question:
We need to find the value of x.
So,
From the given equation:
![(1-3x)^{(1)/(2)}-1=x](https://img.qammunity.org/2023/formulas/mathematics/college/rv25aq3ufu06fgn2fsjcxfm160ecr8yk9u.png)
Then,
Add 1 to both sides of the equation:
So
![\begin{gathered} (1-3x)^{(1)/(2)}-1=x \\ (1-3x)^{(1)/(2)}=x+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7jgkr6ll3zhvrj9foq4dap1jig08pqe0jl.png)
Then,
Square both sides of the above equation:
![\begin{gathered} (1-3x)^{(1)/(2)}=x+1 \\ (1-3x)=(x+1)^2 \\ (1-3x)=x^2+2x+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/75n7mrq5fjca6e3u6ulx23ibxhnz2um0s8.png)
Then,
![\begin{gathered} 1-3x-x^2-2x-1=0 \\ -x^2-5x=0 \\ -x(x+5)=0 \\ x(x+5)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pbdfdncmqeos99nb7abxil1klewhb10q7p.png)
Then,
![\begin{gathered} x(x+5)=0 \\ x=0,x=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dobnavri16dd4eyu4t35otydrzqxxj9u6d.png)
Final answer:
Hence, the correct option is C.